INDICATORS FOR INTEGRATION OF ENVIRONMENTAL CONCERN INTO THE AGRICULTURAL POLICY - Teodor, Cristian (Economics of Agriculture, 2012)
Links between the rich natural environment and farming practices are complex, agriculture continues to be the main user of the countryside, and a determinant factor of landscape and environmental quality, therefore in recent years more attention was paid to the integration of environmental policy objectives in agricultural policy. The paper aims to analyze the main environmental requirements of Common Agricultural Policy in relation to the indicators used to measure integration of environmental concern into the CAP.